Determinants of Sustainable Supply Chain Performance: The role of Corporate Entrepreneurship in Indecision Textile Companies - Endang Noerhartati; Yoyok Soesatyo; Moedjito Moedjito; Toho Cholik Mutohir; Amrozi Khamidi (International Journal of Supply Chain Management, 2020)
This study examined various factors which may enhance the sustainable supply chain activities in Indonesian textile companies. Due to the lack in supply chain operations, the business performance of Indonesian textile companies was not up to the mark. A survey was carried out to collect the primary data. For survey purpose, total 300 questionnaires were distributed among the employees of Indonesian textile companies. By using the Smart PLS 3.0, five hypotheses were tested. During this study, it was revealed that management support and sufficient project time has important role in sustainable supply chain. Supportive organization culture has important role to enhance the positive effect of management support and sufficient project time on sustainable supply chain. It is recommended to the Indonesian textile companies to focus on management support, sufficient project time and organization culture to support sustainable supply chain performance. Therefore, this study is important for the practitioners to enhance textile company’s performance by promoting sustainable supply chain activities.